Studying the bactericidal activity of some newly prepared oxazepine derivatives and characterizing these compounds - Dr.maan ziadan khalaf; Sraa Hussein Kreydie (American Journal of Bioscience and Clinical Integrity, 2026)
The present research focuses on the synthesis and structural investigation of a novel series of oxazepine derivatives obtained though a conventional sublimation-based approach. Interest in seven-membered heterocyclic systems arises from their recognized biological and pharmacological relevance, which has encouraged extensive exploration of their potential applications in medicinal and pharmaceutical sciences. The target compounds were synthesized via cyclization reactions involving 2-aminophenol and a set of chalcone intermediates. These chalcones were initially produced through condensation reactions between substituted scaffold of the study. The prepared derivatives exhibited satisfactory physicochemical properties, along with remarkable stability under standard laboratory conditions. The chemical structures of these compounds were confirmed and their purity assessed using several spectroscopic techniques, including Fourier transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance spectroscopy (1H-NMR), and carbon nuclear magnetic resonance spectroscopy (13C-NMR). Biological evaluation was also conducted to determine the antibacterial activity against representative Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria. The experimental results showed variations in inhibition levels among the prepared molecules, with compound M8 exhibiting the highest activity against Gram-negative strains, followed by compound M10. The inhibitory effect against Gram-positive bacteria was less pronounced compared to the standard antibiotic used for comparison. Ciprofloxacin was used as a standard control, demonstrating higher antibacterial activity than all the prepared derivatives. However, the observed biological responses suggest that the prepared oxazepine compounds could be considered promising prototypical compounds for future development as antimicrobial agents.